Impact of Rainfall on Tropical Cyclone‐Induced Sea Surface Cooling. Issue 10 (20th May 2022) - Balaguru, Karthik; Foltz, Gregory R.; Leung, L. Ruby; Hagos, Samson M.
Abstract: Tropical cyclones (TCs) are often accompanied by strong winds and torrential rains. While the winds associated with TCs tend to enhance mixing in the upper ocean, the freshwater input from rain can stratify the water column and limit mixing. However, the extent to which the stabilizing effect of rainfall can compete with wind‐induced mixing and to what degree it modulates TC‐induced sea surface cooling remain unknown. Here we show, using a suite of observations, that heavy rains under weak TCs can significantly reduce the magnitude of cold wakes induced by them. When compared to storms with low rain rates, the ocean surface under TCs with high rain rates freshens significantly and cools less. High‐resolution climate model simulations and idealized experiments with an ocean mixed layer model support these results and reveal that oceanic mixing processes are primarily responsible for reduced cooling under TCs, with a lesser role for surface fluxes. Plain Language Summary: Strong winds of tropical cyclones (TCs) induce substantial mixing in the upper ocean, a process that entrains colder deeper water into the mixed layer resulting in cooling of the sea surface temperature (SST). Hence, ocean density stratification plays a crucial role in the SST response to TCs and consequently, in their intensification. While most previous studies considered the role of prestorm stratification near the ocean surface on TC‐induced SST cooling, the role of rainfall from TCs in the SST response to storms has mostly remained unexplored. In this study, using a variety of observations, we show that the SST cooling is reduced significantly for weak TCs with large rain rates. Under high rain rates, the upper ocean freshens considerably and the salinity stratification is enhanced. Consequently, vertical mixing and the entrainment of subsurface water is reduced, and the SST cooling decreases. Similar results are obtained using high‐resolution simulations based on the Energy Exascale Earth System Model. Finally, a set of idealized numerical sensitivity experiments with the Price‐Weller‐Pinkel ocean mixed layer model confirm the role of vertical ocean mixing in the rainfall effect on TC‐induced SST change. These results have potential implications for improving our understanding of TC‐ocean interactions. Key Points: Analysis of a suite of observations suggests that high rain rates can reduce the sea surface cooling induced by weak tropical cyclones (TCs) Consistent results are obtained from high‐resolution climate model simulations and sensitivity experiments with an ocean mixed layer model Changes in upper‐ocean stratification and mixing are primarily responsible for the rainfall effect on TC‐induced sea surface temperature cooling